(untitled) (Current Horticulture, 2024)
The precision viticulture aims to optimize grape (Vitis spp. L.) vineyard management; reducing use of resources and environmental impacts; and maximizing quality yield. New technologies as UAVs, satellites, proximal sensors, variable rate machines (VRT) and robots are being developed and used more frequently in some parts of the world in recent years. Developments and abilities of computers, software and informatic systems to read, analyze, process and transfer a huge amount of data are major milestones in precision viticulture. In addition, different decision support systems (DSSs) for making better crop management decisions at the right time also assist vine growers. In the fragmented small vineyards in India, relatively cheaper technologies like UAV, proximal monitoring through various tools, and DSSs developed by the ICAR-NRC for Grapes, Pune, Maharashtra, India can be used by individual grape grower or through farmers’ cooperatives/groups to make grape cultivation technologically-, economically- and environmentally- viable. Therefore, current status of precision viticulture technologies and their potential applications in viticulture, have been discussed.